2019
DOI: 10.1111/1471-0307.12649
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Brazilian consumers regarding white mould surface‐ripened cheese using free word association

Abstract: The aim of this study was to understand the perceptions and/or choices of Brazilian consumers regarding white mould surface-ripened cheeses using the free word association method (FWAM). A total of 350 words, including 'high quality', 'nice', 'beautiful', 'ammonia/milk aroma', 'soft and creamy texture', 'mild flavour' and 'velvety appearance', were used by 408 volunteers. These words were influenced by the cultural diversity of foods. The FWAM can help to develop strategies to strengthen the frequent and occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 24 publications
0
70
2
Order By: Relevance
“…The word association technique encopasses terms that help describe consumers' expectations of a particular product (Eldesouky et al, 2015), so the results obtained by this method can be used to develop or adjust new products (Soares et al, 2017). Judacewski et al (2019) evaluated the study of Brazilian consumers' perceptions of white mold-matured cheeses using the word association technique and concluded that the use of the word association technique made it possible to evaluate the perception of Brazilian consumers (and non-consumers) regarding cheese ripened to the surface by white mold.…”
Section: Resultsmentioning
confidence: 99%
“…The word association technique encopasses terms that help describe consumers' expectations of a particular product (Eldesouky et al, 2015), so the results obtained by this method can be used to develop or adjust new products (Soares et al, 2017). Judacewski et al (2019) evaluated the study of Brazilian consumers' perceptions of white mold-matured cheeses using the word association technique and concluded that the use of the word association technique made it possible to evaluate the perception of Brazilian consumers (and non-consumers) regarding cheese ripened to the surface by white mold.…”
Section: Resultsmentioning
confidence: 99%
“…The perceptions in the choice and acceptance of a food product by consumers are determined by the appearance, aroma, and taste of the food (Judacewski et al., 2019). Based on the color analysis, electronic senses analysis, bioactive compound analysis, and antioxidant activity analysis of 15 JW samples (3 different pretreatment methods × 5 different starter cultures), a data matrix consisting of 15 rows (15 samples) and 27 columns (27 quality indexes compromising 4 color attributes, 10 aroma attributes, 8 taste attributes, 3 bioactive compounds attributes, and 2 antioxidant activity attributes) was obtained, after which multivariate statistical analysis was applied to evaluate the effects of pretreatment methods and starter cultures on JW.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Therefore, viability may not always be the most important aspect in terms incorporating probiotic bacteria in food products. As projective tests, further sensory studies based on innovative methods of consumer perception must be conducted in order to evaluate the impacts of the addition of these microorganisms in food (Chetachukwu et al, 2019;Judacewski et al, 2019;Pinto et al, 2018;Soares et al, 2020).…”
Section: Gelatin:collagen Ratio Microorganismmentioning
confidence: 99%